Joint estimation of interference frequency offset and time delay in PCMA system - Xue-juan WEI; Yong YANG; Yi-ming GUO; Dong-ling ZHANG (Tongxin xuebao)
For cooperative received high-order modulation PCMA (paired carrier multiple access) signals,joint estima-tion of frequency offset and time delay was proposed.The sequence samples stored locally were used as auxiliary data.Estimation of frequency offset and time delay was calculated by optimizing the objective function,which was obtained from the cross-correlation computation of the auxiliary data and mixed signal,and the optimized process was accom-plished by utilizing two-dimensional search.By setting the threshold of joint estimation,the calculated amount was greatly reduced.Modified Cramer-Rao bound (MCRB) of interference frequency offset and time delay was derived,which provided theoretical basis for performance of the proposed algorithm.Simulation results show that the algorithm has similar performance with existing algorithms,but its complexity is reduced by two-thirds.